Epigenome-wide association study of DNA methylation in panic disorder. Issue 1 (December 2017) - Shimada-Sugimoto, Mihoko; Otowa, Takeshi; Miyagawa, Taku; Umekage, Tadashi; Kawamura, Yoshiya; Bundo, Miki; Iwamoto, Kazuya; Tochigi, Mamoru; Kasai, Kiyoto; Kaiya, Hisanobu; Tanii, Hisashi; Okazaki, Yuji; et al.
Abstract Background Panic disorder (PD) is considered to be a multifactorial disorder emerging from interactions among multiple genetic and environmental factors. To date, although genetic studies reported several susceptibility genes with PD, few of them were replicated and the pathogenesis of PD remains to be clarified. Epigenetics is considered to play an important role in etiology of complex traits and diseases, and DNA methylation is one of the major forms of epigenetic modifications. In this study, we performed an epigenome-wide association study of PD using DNA methylation arrays so as to investigate the possibility that different levels of DNA methylation might be associated with PD. Methods The DNA methylation levels of CpG sites across the genome were examined with genomic DNA samples (PD, N = 48, control, N = 48) extracted from peripheral blood. Methylation arrays were used for the analysis.β values, which represent the levels of DNA methylation, were normalized via an appropriate pipeline. Then, β values were converted toM values via the logit transformation for epigenome-wide association study. The relationship between each DNA methylation site and PD was assessed by linear regression analysis with adjustments for the effects of leukocyte subsets. Results Forty CpG sites showed significant association with PD at 5% FDR correction, though the differences of the DNA methylation levels were relatively small. Most of the significant CpG sites (37/40 CpG sites) were located in or around CpG islands. Many of the significant CpG sites (27/40 CpG sites) were located upstream of genes, and all such CpG sites with the exception of two were hypomethylated in PD subjects. A pathway analysis on the genes annotated to the significant CpG sites identified several pathways, including "positive regulation of lymphocyte activation." Conclusions Although future studies with larger number of samples are necessary to confirm the small DNA methylation abnormalities associated with PD, there is a possibility that several CpG sites might be associated, together as a group, with PD.